Profitability in Moderate the Effect of CSR Disclosure on Company Value - Fatiha Fani Anggraeni Supandi (eCo-Buss, 2024)
The goal of this study is to determine the effect of CSR Disclosure using the CSR Disclosure Index (X) on Company Value using the Price to Book Value (Y) through Profitability with the Return on Equity (Z) as a moderating variable with the Company objects listed on the Index SRI - KEHATI Period 2019 – 2023. This study’s population consist of 40 companies listed on the SRI - KEHATI Index for 2019 – 2023. The sample used in this research is 11 companies from a total population of 40 using the purposive sampling method. The data analysis technique used in this research is the Conceptual Model of a Simple Moderation method using SPSS ver 25 software with the add-on PROCESS by M. Hayes. The results of this research show that: (1) CSR Disclosure has a negative and significant effect on Company Value, (2) Profitability has a positive and significant effect on Company Value, (3) Profitability can moderate the relationship between the influence of CSR Disclosure on Company Value.